Contact With an Ex-Partner Is Associated With Psychological Distress After Marital Separation. (May 2020) - O'Hara, Karey L.; Grinberg, Austin M.; Tackman, Allison M.; Mehl, Matthias R.; Sbarra, David A.
In this study, we examined the association between naturalistically observed in-person contact with an ex-partner and separation-related psychological distress (SRPD). One hundred twenty-two recently separated adults were assessed using the Electronically Activated Recorder on three occasions across 5 months. The association between in-person contact with an ex-partner, as a between-person variable, and concurrent SRPD was not reliably different from zero, nor was the time-varying effect of in-person contact. However, more frequent in-person contact with an ex-partner predicted higher SRPD 2 months later, above and beyond the variance accounted for by concurrent in-person contact, demographic, relationship, and attachment factors. Follow-up analyses showed that this effect was present only for people without children; a 1 SD increase in in-person contact offset and slowed the predicted decline in SRPD over 2 months by 112%. In our discussion, we emphasize new ways to think about the role of in-person contact in shaping adults' psychological adjustment to separation over time.